Glycaemic outcomes in Australasian children and adults with type 1 diabetes: failure to meet targets across the age spectrum. Issue 1 (31st May 2022) - Holmes‐Walker, D. Jane; Abraham, Mary B.; Chee, Melissa; Jones, Timothy W.; ,
Abstract: Background: The goal of therapy in type 1 diabetes (T1D) is to achieve optimal glycaemic targets and reduce complications. Robust data representing glycaemic outcomes across the lifespan are lacking in Australasia. Aims: To examine contemporary glycaemic outcomes and rate of use of diabetes technologies in Australasian people with T1D. Methods: Cross‐sectional analysis of de‐identified data from 18 diabetes centres maintained in the Australasian Diabetes Data Network registry during 2019. Glycaemia was measured using glycated haemoglobin (HbA1c). The proportion of people with T1D achieving the international HbA1c target of <53 mmol/mol (7%) was calculated. Rates of continuous subcutaneous insulin infusion (CSII) and continuous glucose monitoring (CGM) use were determined. Results: A total of 7988 individuals with T1D with 30 575 visits were recorded in the registry. The median (interquartile range) age was 15.3 (10.0) years and diabetes duration was 5.7 (9.4) years with 49% on multiple daily injections (MDI) and 36% on CSII. The mean HbA1c for the whole cohort was 66 mmol/mol (8.2%). HbA1c increased with age, from 60 mmol/mol (7.6%) in children <10 years, increasing during adolescence and peaking at 73 mmol/mol (8.8%) in the 20–25 years age group. The HbA1c target of <53 mmol/mol (7%) was met in 18% of children and 13% of adults. HbA1c was lower on CSII as compared with those on MDI ( P < 0.0001). Conclusions: Only a minority of children and adults achieve the recommended glycaemic goals despite access to specialist care in major diabetes centres. There is a need to identify factors that improve glycaemic outcomes.